(untitled) (Global Journal of Human-Social Science, 2021)
This article presents reflections on race and the paths of economic modernization in rural São Paulo, based on other research on the subject. Civilizatory models and projects were offered in order to arrive at an archetype of nation as a proposal on the meaning of land use and custom and the place reserved for blacks in the São Paulo imagination throughout the 20th century. We will make a brief contextualization to understand such transformations, walking between the readings of literary works, such as "Urupês" by Monteiro Lobato and scientific works to understand the representations regarding naturalization, the social and economic legacies of the rural condition, modernization, economic globalization and operation of cooperatives in rural neighborhoods today.